Strategies for pathogen biocontrol using lactic acid bacteria and their metabolites: a focus on meat ecosystems and industrial environments - Castellano, P. (2017)
The globalization of trade and lifestyle ensure that the factors responsible for the emergence of diseases are more present than ever. Despite biotechnology advancements, meat-based foods are still under scrutiny because of the presence of pathogens, which causes a loss of consumer confidence and consequently a fall in demand. In this context, Lactic Acid Bacteria (LAB) as GRAS organisms offer an alternative for developing pathogen-free foods, particularly avoiding Listeria monocytogenes, with minimal processing and fewer additives while maintaining the foods’ sensorial characteristics. The use of LAB strains, enabling us to produce antimicrobial peptides (bacteriocins) in addition to lactic acid, with an impact on quality and safety during fermentation, processing, and/or storage of meat and ready-to-eat (RTE) meat products, constitutes a promising tool. A number of bacteriocin-based strategies including the use of bioprotective cultures, purified and/or semi-purified bacteriocins as well as their inclusion in varied packaging materials under different storage conditions, have been investigated. The application of bacteriocins as part of hurdle technology using non-thermal technologies was explored for the preservation of RTE meat products. Likewise, considering that food contamination with L. monocytogenes is a consequence of the post-processing manipulation of RTE foods, the role of bacteriocinogenic LAB in the control of biofilms formed on industrial surfaces is also discussed.